Critérios para tomada de decisão na escolha de uma empresa turística pelo público da terceira idade - Medeiros, Daniel Céfas de (2018)
This study aimed to bring the light of knowledge how to identify which evaluation criteria that lead senior citizens to opt for a specific tourism company. Regarding to that, the most relevant and important data for the members of the Nova Vida group of the city of Currais Novos/ RN were collected. According to the data collected and analyzed, it is possible to draw a profile of this group and from it, adapt products and itineraries to satisfy their leisure and tourism needs. As well as analyzing consumer behavior, knowing its influence factors and evaluating the alternatives to be deliberated. For that, the quantitative descriptive research, applied through a questionnaire, was used as data collection method. The research was exploratory and descriptive. As for the means, the research was field and bibliographical. The field research universe consisted of the members of the Nova Vida group, which included a director, vice-director, treasurer, secretary, second secretary and other associates, counting 41 individuals. Due to the inability to access all, the sample was non-probabilistic by accessibility, resulting in only 16 associates. Depending on the data analysis, it was possible to perceive that the female gender is predominant, where they are mostly aged between 60 and 65 years, income between 1 and 3 minimum wages, and usually travel once a year. The importance of this study is to identify the most relevant points in the choice of a tourism company, according to the universe of a third age group, knowing their limitations and needs and from them, turning the challenges into opportunities. Finally, through all the study carried out, it is possible to show that the factors of greater relevance for the public of the elderly are centered on services of general service, from the good attendance at the counter, execution of the service acquired, as well as the concern with your well being. With this, we can conclude that it is a mature and demanding public looking for leisure and fun, seeking a serious tourism company with a consolidated brand in the market.